PELATIHAN MUHADHARAH BAGI REMAJA MASJID DALAM MENINGKATKAN KETERAMPILAN BERDAKWAH - Rahmawati Al Ulla; Abdul Ghofur; Aulia Ayu Rohayah (Al-Ihsan: Journal of Community Development in Islamic Studies, 2023)
As a teenager of mosque should have the ability to preach or at least have the courage to speak in public. However, the fact is that mosque youth, especially in the Kaliabang Tengah RW 013 sub-district, still do not have more confidence to speak in public. Thus, with such problems it is necessary to have activities aimed at developing skills, especially in terms of giving speeches and also preaching. So the right method to deal with these problems is to use the da'wah training method. The implementation is by implementing the muhadharah strategy. Through this muhadharah, mosque youth will be trained to speak like a preacher who is preaching. Muhadharah activities are equipped with da'wah techniques and convey propaganda messages with the intention that they have the courage to speak in public. This training activity will be carried out by providing material, training for each individual and then there will be an evaluation at the end of the activity. This research was carried out using training which in the process would involve youth mosques in the Kaliabang Tengah village, especially in the RW 013 environment.